Salient beliefs and intention to shop online - Adam, Mohamad Zainol Abidin; Nik Mat, Nik Kamariah (2006)
This paper examines the relationships between salient beliefs and intention to shop online based on TRA model.Over 140 students of a Malaysian university completed a 4-page questionnaire consisting of 26-items measuring salient beliefs(convenience, information, product perception, shopping experience, customer service and customer risk) and 4-items measuring intention to shop online for 18 product categories.Regression analysis of factor scores (resulting from factor analysis of salient beliefs) shows that convenience, information and product perception jointly explain 43.5 percent variance in intention to shop online.The finding implies that online shopping is becoming more popular amongst students due to its convenience, ease of getting information and positive product perceptions.This implies that E-commerce operators should continue to make their presence known on the web. Limitations and practical implications of the findings are also discussed in the paper.